Characteristics, sources, and health risks of PM2.5-bound trace elements in representative areas of Northern Zhejiang Province, China. (June 2021) - Xu, Jingsha; Jia, Chunrong; Yu, Huan; Xu, Honghui; Ji, Dongsheng; Wang, Chengjun; Xiao, Hang; He, Jun
Abstract: This study aimed to characterize PM2.5 -bound trace elements in Northern Zhejiang Province (NZP), one of the most economically prosperous regions in China, and assess the associated health risks for the general populations. A year-long sampling campaign was conducted at four sites representative of urban, suburban, and rural areas of NZP. The average of the sum of twenty trace elements in PM2.5 was 2.8 ± 0.4 μg m −3, dominated by K, Al, Fe, Mg, Zn, and V (>100 ng m −3 ). The highest total elements' concentration occurred in winter, followed by autumn, spring, and summer. Enrichment factors and principal component analysis (PCA) revealed that the major sources of trace elements in NZP were fossil fuel combustion, biomass burning, crustal dust, traffic, and industrial emissions. Elevated concentrations of certain elements reflected featured sources in different areas, e.g., V and Ni from heavy oil combustion in the port city, and Cu, Fe and Ba from traffic emissions in urban areas. Arsenic (As) represented the major non-cancer risk driver as its hazard quotient was 8.7. The cumulative cancer risk from all the carcinogenic elements was 1.7 × 10 −3 in NZP, exceeding the upper limit (10 −4 ) of the acceptable risk range. As and Cr contributed 33% and 66%, respectively, and thus were regarded as cancer risk drivers. The high health risks from PM2.5 -bound elements warrant future actions to control their emissions in this region. Priorities should target industrial operations and coal combustion emissions, as informed by the risk drivers. Graphical abstract: Image 1 Highlights: Trace element levels exhibited a seasonality of winter > autumn > spring > summer. Elements were mostly anthropogenic except for Mg, Sr, and Fe. Shipping emissions dominated the port city. Arsenic was the non-cancer risk driver with a hazard quotient of 8.7. The cumulative cancer risk was 1.7 × 10 −3, with chromium and arsenic as drivers.